Revisional notes on Iolaus aequatorialis Stempffer Bennett, 1958 and related species in the subgenus Philiolaus Stempffer Bennett, 1958 (Lepidoptera, Lycaenidae, Theclinae), with description of two new species - Sáfián, Szabolcs; Collins, Steve C. (Zootaxa, 2022)
Similarities in male and female genitalic structure isolate a small group of taxa in the genus Iolaus Hübner, [1819], subgenus Philiolaus Stempffer & Bennett, 1958, related to Iolaus aequatorialis Stempffer & Bennett, 1958. They are assigned to the newly proposed I. aequatorialis species group with two new species recognised and described. This action also clarifies previous taxonomic misunderstandings involving a few other species with similar facies because of a lack of information on male and female genital morphology.